KONSEP PENDIDIKAN KARAKTER TERHADAP NORMA SUSILA DI SEKOLAH DASAR - Mhd Arif Setiawan (At-Tazakki: Jurnal Kajian Ilmu Pendidikan Islam dan Humaniora, 2022)
Abstract: Character formation cannot be done by memorizing, because this is inherent in every human being and depends on self-ability. Character can only be taught to the younger generation by example and example. The purpose of this study is to describe the concept of character education against moral norms in schools, especially in elementary schools. This study uses a literature study method that relies on bibliographic sources from books and articles in scientific journals related to the subject matter. The results of this study indicate that: 1) The concept of character education against moral norms can be applied through: a) exemplary, b) discipline, c) habituation, d) creating a conducive atmosphere. 2) Implementation of character education on moral norms with a) moral knowing, b) perspective taking, c) moral feeling, d) moral avtion. Keywords: Character Education, Moral Norms, Elementary School